METHODOLOGY OF TEACHING ENGLISH PROVERBS TO B1 LEVEL LEARNERS - Kambarova Marjan Adil kizi (Western European Studies, 2025)
The proverb, as a paremiological cliche, is studied from different scientific positions, which are based on different methodological approaches, which leads experts to different ways of its research. The study and teaching of the proverbial material of a non-native (English) language has great linguistic and methodological significance. The knowledge of proverbs of foreign languages will contribute to the improvement of theoretical and practical knowledge; will help to reveal the culture, history, the way of life of the people; will aid to build more conscious interethnic correct implementation of interlanguage and intercultural communication, which improves the bilingual and communicative competence of students.
Keywords: proverb; English; methodology; sound